Meningkatkan potensi kewirausahaan dan inovasi produk jamu di SMKN 1 Mojosongo Boyolali - Agustina Intan Niken Tari; Catur Budi Handayani; Novian Wely Asmoro (LPPM Universitas Narotama, 2025)
Entrepreneurship is one of the competency demands of graduates of SMK Negeri 1 Mojosongo. This competency is one of the indicators of the quality of human resources of SMK graduates. One of the efforts made is to instill an interest in entrepreneurship among its students, through the concept of cooperation with various parties, including the Agricultural Product Technology study program of Veteran Bangun Nusantara University. This concept of cooperation is in the form of knowledge transfer packaged in community service activities. This activity has several stages starting from identifying partner problems, namely the need to understand the concept of entrepreneurship, business plans, design concepts and innovations of contemporary herbal medicine products and business marketing. In the early stages of the activity, students were asked to take a pretest to determine the initial level of understanding. The second stage is the presentation of entrepreneurship material and discussion, the third stage is counseling on business plans, the fourth stage is counseling as well as a demonstration / direct practice of making contemporary herbal medicine product innovations. The activity ended with a post-test and testimonials on the results of the activity. The results of the community service showed an increase in knowledge of 25.64%.